Green Composites from Sustainable Cellulose Nanofibrils - MartÃnez-Barrera, Gonzalo; Garduño-Jaimes, Irna Zukeyt; Vigueras Santiago, Enrique; Cruz-Olivares, Julián; González-Rivas, Nelly; Gençel, Osman Serden (Springer Nature, 2021)
The current needs are engines for the development of novel materials and sustainable technologies, which are being carried out by research groups in order to achieve better solutions for our daily life. In this chapter, cellulose nanofibrils (CNFs) are studied, according to their synthesis, properties and technological applications. One of these related to produce green nanocomposites, which are based mainly on the environmentally friendly materials. Future trends on the production processes and their multifunctional applications are boarded. In the last section, an ongoing research about cellulose nanofibers is mentioned. © 2022 Elsevier B.V., All rights reserved.
Keywords: Bacterial Cellulose; Cellulose Nanofibrils; Electrospinning; Green Composites